Virulence and antibiotic resistance plasticity of Arcobacter butzleri: Insights on the genomic diversity of an emerging human pathogen - Isidro, Joana (2020)
Arcobacter butzleri is a foodborne emerging human pathogen, frequently displaying a multidrug resistant character. Still, the lack of comprehensive genome-scale comparative analysis has limited our knowledge on A. butzleri diversification and pathogenicity. Here, we performed a deep genome analysis of A. butzleri focused on decoding its core- and pan-genome diversity and specific genetic traits underlying its pathogenic potential and diverse ecology. A. butzleri (genome size 2.07-2.58 Mbp) revealed a large open pan-genome with 7474 genes (about 50% being singletons) and a small but diverse core-genome with 1165 genes. It presents a plastic virulome (including newly identified determinants), marked by the differential presence of multiple adaptation-related virulence factors, such as the urease cluster ureD(AB)CEFG (phenotypically confirmed), the hypervariable hemagglutinin-encoding hecA, a type I secretion system (T1SS) harboring another agglutinin and a novel VirB/D4 T4SS likely linked to interbacterial competition and cytotoxicity. In addition, A. butzleri harbors a large repertoire of efflux pumps (EPs) and other antibiotic resistant determinants. We unprecedentedly describe a genetic mechanism of A. butzleri macrolides resistance, (inactivation of a TetR repressor likely regulating an EP). Fluoroquinolones resistance correlated with Thr-85-Ile in GyrA and ampicillin resistance was linked to an OXA-15-like β-lactamase. Remarkably, by decoding the polymorphism pattern of the main antigen PorA, we show that A. butzleri is able to exchange porA as a whole and/or hypervariable epitope-encoding regions separately, leading to a multitude of chimeric PorA presentations that can impact pathogen-host interaction during infection. Ultimately, our unprecedented screening of short sequence repeats indicates that phase variation likely modulates A. butzleri key adaptive functions. In summary, this study constitutes a turning point on A. butzleri comparative genomics revealing that this human gastrointestinal pathogen is equipped with vast and diverse virulence and antibiotic resistance arsenals that open a multitude of phenotypic fingerprints for environmental/host adaptation and pathogenicity.